2012
DOI: 10.1242/dmm.009563
|View full text |Cite
|
Sign up to set email alerts
|

Muscleblind, BSF and TBPH are mislocalized in the muscle sarcomere of aDrosophilamyotonic dystrophy model

Abstract: SUMMARYMyotonic dystrophy type 1 (DM1) is a genetic disease caused by the pathological expansion of a CTG trinucleotide repeat in the 3′ UTR of the DMPK gene. In the DMPK transcripts, the CUG expansions sequester RNA-binding proteins into nuclear foci, including transcription factors and alternative splicing regulators such as MBNL1. MBNL1 sequestration has been associated with key features of DM1. However, the basis behind a number of molecular and histological alterations in DM1 remain unclear. To help ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 64 publications
(95 reference statements)
2
45
0
Order By: Relevance
“…To further analyze the effect of dme-miR-277 or dme-miR-304 silencing we stained Muscleblind distribution in longitudinal sections of indirect flight muscles (IFMs). We had previously shown that endogenous Muscleblind protein is localized mainly in sarcomeric Z and H bands of muscle42. Consistently, we detected Muscleblind proteins in the bands of muscle sarcomeres in control flies that express the scramble-SP construct (Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…To further analyze the effect of dme-miR-277 or dme-miR-304 silencing we stained Muscleblind distribution in longitudinal sections of indirect flight muscles (IFMs). We had previously shown that endogenous Muscleblind protein is localized mainly in sarcomeric Z and H bands of muscle42. Consistently, we detected Muscleblind proteins in the bands of muscle sarcomeres in control flies that express the scramble-SP construct (Fig.…”
Section: Resultssupporting
confidence: 86%
“…The recombinant line Mhc-Gal4 UAS-i(CTG)480 was generated in ref. 42. UAS-mblC flies58 and UAS-IR-mbl flies42 were previously reported.…”
Section: Methodsmentioning
confidence: 91%
“…Interestingly, the expansion of CTG trinucleotide repeats in the 3′ UTR of the DMPK gene (responsible for myotonic dystrophy type 1 (DM1)) could sequester TBPH and other related proteins into nuclear foci, thus depriving cell of these vital protein functions (Llamusi et al 2013) (Fig. 4d), with a mechanism remembering the previously described interaction between Hrb87F and the CGG trinucleotide repeat at the 5′ untranslated region of FMR1 gene (Fig.…”
Section: Roles In Neuromuscular Developmentmentioning
confidence: 81%
“…Furthermore, an interaction between TBPH and the dystrophia myotonica-protein kinase (DMPK) gene has also been recently identified (Llamusi et al 2013). Interestingly, the expansion of CTG trinucleotide repeats in the 3′ UTR of the DMPK gene (responsible for myotonic dystrophy type 1 (DM1)) could sequester TBPH and other related proteins into nuclear foci, thus depriving cell of these vital protein functions (Llamusi et al 2013) (Fig.…”
Section: Roles In Neuromuscular Developmentmentioning
confidence: 99%
“…As regulators of alternative splicing both CELF and MBNL proteins typically bind to the introns downstream or upstream of an alternative exon to promote inclusion or exclusion, respectively (Kalsotra et al, 2008; Wang et al, 2012). In the cytoplasm, MBNL affects mRNA localization or stability by binding the 3’ UTR of target mRNAs (Llamusi et al, 2013; Masuda et al, 2012). …”
Section: Celf and Mbnl In Dmmentioning
confidence: 99%